MECHANICAL ENHANCEMENT OF POLYMER COMPOSITES USING IRON OXIDE NANOPARTICLES: A REVIEW - Salman Afzal,; Tasneem Kosar,; Ayesha Hassan,; Muhammad Rashid, (Spectrum of Engineering Sciences, 2025)
Polymer matrix composites (PMCs) have gained prominence for their light weight, corrosion resistance, and low cost; however, their poor mechanical strength limits their use in high-performance applications. This review focuses on the role of iron oxide nanoparticles (Fe₃O₄ and γ-Fe₂O₃) in enhancing the mechanical properties of PMCs through mechanisms such as improved stress transfer, crack resistance, and interface strength. This study includes a detailed analysis of the effect of nanoparticle parameters; such as size, surface functionalization, dispersion quality, and orientation on mechanical behavior. It also explores recent developments in hybrid nanofillers, magnetic alignment techniques, and smart functionalities like shape-memory effects and electromagnetic responsiveness. This study further reviews advanced processing methods such as in-situ polymerization and green synthesis, highlighting their advantages in achieving uniform dispersion and environmental compatibility. A special focus is placed on interface engineering and stress transfer mechanisms, supported by modern characterization techniques like Raman spectroscopy and electron microscopy. Additionally, the review compiles key challenges in nanoparticle dispersion, alignment, and scale-up, along with their contributing causes. To offer practical insights, categorized tables summarize performance outcomes, processing conditions, and recurring fabrication issues. Hence, this comprehensive study aims to provide researchers with both foundational understanding and advanced insights into the development of high-performance, multifunctional Fe₃O₄-reinforced polymer nanocomposites.